Use of a New Comprehensive Insurance Benefit for Smoking-Cessation Treatment - Marguerite E. Burns, MA; Marjorie A. Rosenberg, PhD; Michael C. Fiore, MD, MPH (Centers for Disease Control and Prevention, 2005)
Introduction Uncertainty about levels of employee use of an insurance benefit for smoking-cessation treatment has presented a barrier to employers considering the adoption of such coverage. This study examined self-reported awareness and use of a new insurance benefit for smoking-cessation treatment among a sample of Wisconsin state employees, retirees, and adult dependents. Methods We evaluated the self-reported use of insurance coverage for smoking-cessation treatment during the first 2 years of its availability to the Wisconsin state employee, retiree, and adult dependent population. We conducted analyses of responses to smoking-related questions in 2001 and 2002 cross-sectional surveys of insured state employees, retirees, and adult dependents, weighted to represent this population. Results In 2002, benefit use among smokers aware of the benefit was 39.6%, and benefit use among smokers unaware of the benefit was 3.5%. Only 27.4% of smokers were aware of the benefit in 2002; use among all smokers was 13.6%. Of all smokers, 30.4% used smoking-cessation treatment medication (over-the-counter or covered) in 2002. Smoking prevalence was 15.6% in 2001 and 13.2% in 2002. Conclusion In an educated employee population, self-reported smoking-cessation treatment benefit use was modest among all smokers during its first 2 years of availability. Benefit awareness was low in this educated population, which may help explain low use rates, particularly given the 30% of all smokers who attempted to quit smoking with the help of smoking-cessation treatment medication. These data provide use-rate estimates for states contemplating adoption of an evidence-based smoking-cessation treatment benefit.